Attribution theory of poverty and beliefs about charity in Malaysia: an inter-ethnic comparison - Khan, Abidullah; Shafiai, Muhammad Hakimi Mohd; Abbas, Ghulam; Zaidi, Syeda Beena; Hassan, Mehboob Ul (Frontiers in Psychology, 2025)
IntroductionMalaysia as an ethnically diverse country has a history of interethnic inequality and poverty which led to the development of different views about the existence of poverty. Among these ethnic groups, some sympathize with the poor and help them through different charity organizations. However, these charity organizations are mostly unaware of the target donors that can aid their charity funds. Therefore, this study explores the attitudinal differences regarding poverty among Malays, Chinese, and Indians and the demographic groups that can be targeted for donation and social policy development purposes.MethodologyA survey is conducted in Selangor, where the data through a questionnaire is extracted from the three ethnic groups. Through the quota sampling technique, a sample of 700 is derived. The results are analyzed through ANOVA, regression, and mediation analysis.ResultsThe results show that attitudinal differences between Malays and Chinese regarding structuralist beliefs could be observed. Moreover, among Malays, it is found that the relationship between gender, income, education, wealth, and structuralist beliefs is significantly mediated by beliefs about charity. On the other hand, mediation analysis for Chinese identifies gender, education, and income while among Indians gender, education, and wealth are identified as key demographic groups.DiscussionThis study highlights the role of attribution theory to identify the charity donors among the different ethnic groups which was overshadowed by the previous research in Malaysia. The results also hold significance for charity institutions to target the specified groups through their marketing campaigns. Also, based on these results government can reduce the misconception about the existence of poverty and to develop policies that encourage high income groups to support the poor.